2016
DOI: 10.24959/ubphj.16.34
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological predication of using of vaginal suppositories "melanizol" for treatment nonspecific vaginitis

Abstract: The article considers the vaginal suppositories "Melanizol" based on metronidazole, and tea tree oil influence on the museum and clinical microorganisms strains, that may be potential agents of vaginal infections. Established antimicrobial activity of vaginal suppositories "Melanizol" against the following strains of microorganisms Staphylococcus aureus, Basillus subtilis, Klebsiella, and Escherichia coli, and also found their antifungal activity against Candida albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…3. The preliminary studies proved anti-inflammatory [22], antibacterial [23] properties of the new vaginal suppositories "Melanizol", and the antioxidant activity proved by us in this experiment allow to recommend them for the further studies as drug for the treatment of nonspecific vaginitis.…”
Section: Discussionmentioning
confidence: 83%
“…3. The preliminary studies proved anti-inflammatory [22], antibacterial [23] properties of the new vaginal suppositories "Melanizol", and the antioxidant activity proved by us in this experiment allow to recommend them for the further studies as drug for the treatment of nonspecific vaginitis.…”
Section: Discussionmentioning
confidence: 83%
“…On the pharmaceutical market of Ukraine, drugs that are presented for the treatment of NV [6] have both advantages and numerous side properties. In previous studies, we have found that suppositories of "Melanizol" show expressive anti-inflammatory [7] and antimicrobial [8] effect. These properties have led to the feasibility of experimental studies of suppositories "Melanizol" as a treatment for vaginitis.…”
Section: Planning (Methodology) Of Researchmentioning
confidence: 99%